Former Yugoslav Republic of Macedonia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper and Statistical Appendix formulates a medium-term fiscal framework for the Former Yugoslav Republic of Macedonia (FYRM) and discusses the tensions that are likely to arise in formulating policy measures. The paper reviews recent fiscal developments and the 2002 budget. It discusses medium-term revenue and expenditure issues, the uncertainties and risks underlying the fiscal framework, and the sensitivity of the fiscal outlook to some of these uncertainties and risks. The paper also compares the size and structural aspects of FYRM's public finances to those of other countries in the region.